Dziecięca ikonografia księżniczek Okresu Amarneńskiego - Kloska, Maria Monika (Folia Praehistorica Posnaniensia, 2018)
This article explains the characteristic style of princesses representations in Amarna Period art. This high essential aspect (in literally way) shows full of love relations between family members from Akhetaten. Children iconography in ancient Egypt remained rather persistent, however, pictures showing Meritaten, Maketaten, Ankhesenpaaten, Neferneferuaten, Neferneferure and Setepenre stand alone not only by details, but also by scenes in which princesses have been presented. The royal daughters are often shown naked or in robes looking like delicate tied with sash in waist or under bust dress belonging to their mother Nefertiti. Though girls – regardless of age – have always been portrayed with the sidelock of youth. The reliefs representing Amarna princesses and their parents deviate significantly from fixed and formal style of iconography which is characteristic for periods before and after Akhenaten’s reigns. The girls have been shown not only in family scenes enjoying a good time with their parents, but also accompanying the royal couple in scenes of tribute from Nubia and Syria, in the scenes of killing enemies of Egypt and in the heart-touching mourning scenes. The representations of the six daughters of Akhenaten and Nefertiti, besides being the symbol of the spouses’ fertility, also performed an important religious function – the girls together with their parents and the god Aten created the divine Ennead just like the model of the nine gods from Heliopolis. The reliefs showing Amarna family seem to present real feelings and emotions of the royal couple and their children, although it could have a propagandist character.